Plug-and-play education : knowledge and learning in the age of platforms and artificial intelligence - Perrotta, Carlo (New York, NY : Routledge, 2024)
"Plug-and-Play Education: Knowledge and Learning in the Age of Platforms and Artificial Intelligence documents and critiques how the education sector is changing with the advancement of ubiquitous ed tech platforms and automation. As programmability and computation reengineer institutions toward efficiency and prediction, the perpetual collection of and access to digital data is creating complex opportunities and concerns. Drawing from research into secondary and higher education settings, this book examines the influence of digital "infrastructuring," the automation of teaching and learning, and the very purpose of education in a context of growing platformisation and artificial intelligence integration. These theoretical, practical, and policy-oriented insights will offer educational technologists, designers, researchers, and policymakers a more inclusive, diverse, and open-ended perspective on the design and implementation of learning technologies"--
Keywords: Education -- Effect of technological innovations on; Artificial intelligence -- Educational applications; Education -- Aims and objectives; EDUCATION / Distance Education & Learning; EDUCATION / Organizations & Institutions; EDUCATION / Educational Policy & Reform / General